Наукова і громадська діяльність Д. І. Багалія - Лисенко, А. А. (ХНУРЕ, 2020)
The paper is dedicated to the topic of the work of the renowned scientist, Dmytro Bagaliy, who worked primarily in the fields of civil and public relations as well as history-related topics such as library, museum and archive affairs. The author has outlined the importance of his work, which had been understated in previous works of this period and put emphasis on his achievement of investigating the history of Slobidska Ukraine. The conclusion comprises author’s opinion on his place among others for the development of the Ukrainian culture. Дослідження життя і діяльності видатних представників науки і культури Слобожанщини є актуальною проблемою. Яскравим представником цієї плеяди видатних особистостей є Д. І. Баталій.
Keywords: культурне розмаїття; українознавство